Trigonometry Examples

Find the Inverse y=arcsin((x+3)/4)
y=arcsin(x+34)
Step 1
Interchange the variables.
x=arcsin(y+34)
Step 2
Solve for y.
Tap for more steps...
Step 2.1
Rewrite the equation as arcsin(y+34)=x.
arcsin(y+34)=x
Step 2.2
Take the inverse arcsine of both sides of the equation to extract y from inside the arcsine.
y+34=sin(x)
Step 2.3
Simplify the left side.
Tap for more steps...
Step 2.3.1
Split the fraction y+34 into two fractions.
y4+34=sin(x)
y4+34=sin(x)
Step 2.4
Subtract 34 from both sides of the equation.
y4=sin(x)-34
Step 2.5
Multiply both sides of the equation by 4.
4y4=4(sin(x)-34)
Step 2.6
Simplify both sides of the equation.
Tap for more steps...
Step 2.6.1
Simplify the left side.
Tap for more steps...
Step 2.6.1.1
Cancel the common factor of 4.
Tap for more steps...
Step 2.6.1.1.1
Cancel the common factor.
4y4=4(sin(x)-34)
Step 2.6.1.1.2
Rewrite the expression.
y=4(sin(x)-34)
y=4(sin(x)-34)
y=4(sin(x)-34)
Step 2.6.2
Simplify the right side.
Tap for more steps...
Step 2.6.2.1
Simplify 4(sin(x)-34).
Tap for more steps...
Step 2.6.2.1.1
Apply the distributive property.
y=4sin(x)+4(-34)
Step 2.6.2.1.2
Cancel the common factor of 4.
Tap for more steps...
Step 2.6.2.1.2.1
Move the leading negative in -34 into the numerator.
y=4sin(x)+4(-34)
Step 2.6.2.1.2.2
Cancel the common factor.
y=4sin(x)+4(-34)
Step 2.6.2.1.2.3
Rewrite the expression.
y=4sin(x)-3
y=4sin(x)-3
y=4sin(x)-3
y=4sin(x)-3
y=4sin(x)-3
Step 2.7
Subtract 34 from both sides of the equation.
y4=sin(x)-34
Step 2.8
Multiply both sides of the equation by 4.
4y4=4(sin(x)-34)
Step 2.9
Simplify both sides of the equation.
Tap for more steps...
Step 2.9.1
Simplify the left side.
Tap for more steps...
Step 2.9.1.1
Cancel the common factor of 4.
Tap for more steps...
Step 2.9.1.1.1
Cancel the common factor.
4y4=4(sin(x)-34)
Step 2.9.1.1.2
Rewrite the expression.
y=4(sin(x)-34)
y=4(sin(x)-34)
y=4(sin(x)-34)
Step 2.9.2
Simplify the right side.
Tap for more steps...
Step 2.9.2.1
Simplify 4(sin(x)-34).
Tap for more steps...
Step 2.9.2.1.1
Apply the distributive property.
y=4sin(x)+4(-34)
Step 2.9.2.1.2
Cancel the common factor of 4.
Tap for more steps...
Step 2.9.2.1.2.1
Move the leading negative in -34 into the numerator.
y=4sin(x)+4(-34)
Step 2.9.2.1.2.2
Cancel the common factor.
y=4sin(x)+4(-34)
Step 2.9.2.1.2.3
Rewrite the expression.
y=4sin(x)-3
y=4sin(x)-3
y=4sin(x)-3
y=4sin(x)-3
y=4sin(x)-3
y=4sin(x)-3
Step 3
Replace y with f-1(x) to show the final answer.
f-1(x)=4sin(x)-3
Step 4
Verify if f-1(x)=4sin(x)-3 is the inverse of f(x)=arcsin(x+34).
Tap for more steps...
Step 4.1
To verify the inverse, check if f-1(f(x))=x and f(f-1(x))=x.
Step 4.2
Evaluate f-1(f(x)).
Tap for more steps...
Step 4.2.1
Set up the composite result function.
f-1(f(x))
Step 4.2.2
Evaluate f-1(arcsin(x+34)) by substituting in the value of f into f-1.
f-1(arcsin(x+34))=4sin(arcsin(x+34))-3
Step 4.2.3
Simplify each term.
Tap for more steps...
Step 4.2.3.1
The functions sine and arcsine are inverses.
f-1(arcsin(x+34))=4(x+34)-3
Step 4.2.3.2
Cancel the common factor of 4.
Tap for more steps...
Step 4.2.3.2.1
Cancel the common factor.
f-1(arcsin(x+34))=4(x+34)-3
Step 4.2.3.2.2
Rewrite the expression.
f-1(arcsin(x+34))=x+3-3
f-1(arcsin(x+34))=x+3-3
f-1(arcsin(x+34))=x+3-3
Step 4.2.4
Combine the opposite terms in x+3-3.
Tap for more steps...
Step 4.2.4.1
Subtract 3 from 3.
f-1(arcsin(x+34))=x+0
Step 4.2.4.2
Add x and 0.
f-1(arcsin(x+34))=x
f-1(arcsin(x+34))=x
f-1(arcsin(x+34))=x
Step 4.3
Evaluate f(f-1(x)).
Tap for more steps...
Step 4.3.1
Set up the composite result function.
f(f-1(x))
Step 4.3.2
Evaluate f(4sin(x)-3) by substituting in the value of f-1 into f.
f(4sin(x)-3)=arcsin((4sin(x)-3)+34)
Step 4.3.3
Simplify the numerator.
Tap for more steps...
Step 4.3.3.1
Add -3 and 3.
f(4sin(x)-3)=arcsin(4sin(x)+04)
Step 4.3.3.2
Add 4sin(x) and 0.
f(4sin(x)-3)=arcsin(4sin(x)4)
f(4sin(x)-3)=arcsin(4sin(x)4)
Step 4.3.4
Cancel the common factor of 4.
Tap for more steps...
Step 4.3.4.1
Cancel the common factor.
f(4sin(x)-3)=arcsin(4sin(x)4)
Step 4.3.4.2
Divide sin(x) by 1.
f(4sin(x)-3)=arcsin(sin(x))
f(4sin(x)-3)=arcsin(sin(x))
f(4sin(x)-3)=arcsin(sin(x))
Step 4.4
Since f-1(f(x))=x and f(f-1(x))=x, then f-1(x)=4sin(x)-3 is the inverse of f(x)=arcsin(x+34).
f-1(x)=4sin(x)-3
f-1(x)=4sin(x)-3
 [x2  12  π  xdx ]